Calculating Mass Balance And Energy Balance In Finish Mill 6 (6zi) Type Opc Using Purified Gypsum - Patimah, Sri; Hasannah, Cintiya Septa (Peneliti.net, 2024)
PT Semen Padang is the first cement factory in Indonesia which is located in Indarung, Padang, West Sumatra Province. The raw materials in the cement manufacturing process at PT Semen Padang use four main raw materials, namely, limestone, silica, clay and iron sand and additional raw materials such as gypsum and pozzolan. In general, the process of making cement at PT Semen Padang is divided into 5 stages, namely: the raw material supply and preparation stage, the raw material grinding stage (raw mix formation), the clinker formation stage (raw mix burning) the clinker grinding stage (cement manufacture) and the cement manufacturing stage. cement bagging. The total cement production capacity at PT Semen Padang from Indarung 1 to VI is 10,070,000 tons/year. PT Semen Padang's market share for marketing Portland Cement Type 1, Super Mansory Cement (SMC) and Portland Pozzolan Cement (PCC) products, namely in all provinces on the island of Sumatra, DKI Jakarta, Banten, West Java, Central Java, West Kalimantan and South Kalimantan.